DINAMIKA EWOM, SIKAP, DAN NIAT MEMBELI: ANALISIS EMPIRIS PADA KONSUMEN PRODUK THRIFTING - Kurniawan, Sabda Aji; Tabelessy, Walter (ITB AAS Indonesia Surakarta, 2025)
The rapid development of social media has positioned electronic word of mouth (eWOM) as a primary source of information influencing consumer behavior, including in the context of thrifting product purchases. This study aims to examine the effect of eWOM on purchase intention, emphasizing the mediating role of consumer attitude. Data were collected through an online questionnaire administered to 100 respondents using a convenience sampling method and analyzed with variance-based structural equation modeling (SEM) via Adanco software. The results reveal that eWOM significantly influences consumer attitude but does not exert a direct effect on purchase intention. Conversely, consumer attitude demonstrates a strong positive impact on purchase intention and mediates the relationship between eWOM and purchase intention. These findings highlight that the effectiveness of eWOM is more substantial when processed through consumers’ cognitive and evaluative mechanisms that shape positive attitudes before driving purchase decisions. Theoretically, this study contributes to extending the understanding of psychological dynamics in consumer behavior, while practically it offers implications for thrifting businesses to leverage eWOM-based communication strategies in fostering positive attitudes as a preliminary step to enhancing purchase intention.